2020
DOI: 10.3390/ma13102366
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Retention of Calcium Zirconium Aluminate Cement Paste Studied by NMR, XRD and SEM-EDS

Abstract: This work concerns the hydration mechanism of calcium zirconium aluminate as a ternary compound appearing in the CaO-Al2O3-ZrO2 diagram besides the calcium aluminates commonly used as the main constitutes of calcium aluminate cements (CACs). Moreover, a state-of-the-art approach towards significant changes in hydraulic properties was implemented for the first time in this work, where the effect of structural modification on the hydration behavior of calcium zirconium aluminate was proved by XRD, 27Al MAS NMR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…These admixtures modify the hydration behavior, contributing to the adaptation of the cementitious materials to the site conditions. Madej [8] showed that the substitution of Sr 2+ for Ca 2+ in the Ca 7 ZrAl 6 O 18 lattice decreased the reactivity of Sr-substituted Ca 7 ZrAl 6 O 18 in the presence of water. Therefore, strontium can be considered an inhibition agent for cement hydration.…”
mentioning
confidence: 99%
“…These admixtures modify the hydration behavior, contributing to the adaptation of the cementitious materials to the site conditions. Madej [8] showed that the substitution of Sr 2+ for Ca 2+ in the Ca 7 ZrAl 6 O 18 lattice decreased the reactivity of Sr-substituted Ca 7 ZrAl 6 O 18 in the presence of water. Therefore, strontium can be considered an inhibition agent for cement hydration.…”
mentioning
confidence: 99%